2020
DOI: 10.1001/jamanetworkopen.2019.20352
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Real-Time Locator System to Identify Physician and Nurse Work Locations

Abstract: had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
(2 reference statements)
1
9
0
Order By: Relevance
“…Not unexpectedly and consistent with prior findings [ 14 , 32 ], we observed that nurses, compared to physicians, had the majority of interactions (81% of entrances and 85% of the time) with patients under evaluation for COVID-19. Thus, telemedicine technologies may hold greater potential to impact nursing workflows to decrease transmission risk in a pandemic compared to other health care clinicians; however, additional research is needed to understand what elements of nursing work can be done virtually while maintaining high-quality patient care [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Not unexpectedly and consistent with prior findings [ 14 , 32 ], we observed that nurses, compared to physicians, had the majority of interactions (81% of entrances and 85% of the time) with patients under evaluation for COVID-19. Thus, telemedicine technologies may hold greater potential to impact nursing workflows to decrease transmission risk in a pandemic compared to other health care clinicians; however, additional research is needed to understand what elements of nursing work can be done virtually while maintaining high-quality patient care [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Stanford Health Care (SHC) launched an RTLS platform (Midmark) in conjunction with the opening of a new hospital building in late 2019. Infrared and radiofrequency sensors were installed in every patient care room, and staff were given RTLS badges to wear alongside their name badge [ 14 , 26 ]. The RTLS system required line of sight between the room sensor and staff member’s badge to trigger.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of a hands-on physical examination—both for diagnostic and therapeutic purposes—is evidenced in the literature [ 51 , 52 ], but how to best adapt these learnings to patients are under isolation precautions remains an open question. Nurses were reported to use telemedicine more frequently than physicians, while also maintaining a frequent physical presence within the room, which is perhaps unsurprising given that nurses spend approximately 6-fold more time at the patient bedside than physicians in non–COVID-19 settings [ 53 , 54 ]. These COVID-19 data further validate past qualitative work, which suggests that nurses use telemedicine as a bridge to in-person care and “batch” care activities, such that physical assessment, medication delivery, meal delivery, and sanitation protocols all occur in a single room entry [ 27 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“… 18 However, they require trained observers shadowing participants and have logistical challenges and high costs. Methods that use a real-time locating system (RTLS) 19 , 20 may be a more scalable approach for graduate medical training programs. 21…”
Section: Introductionmentioning
confidence: 99%